Ferula asafoetida: Traditional uses and pharmacological activity - Mahendra, Poonam; Bisht, Shradha (Pharmacognosy Reviews, 2012)
Ferula asafoetida is herbaceous plant of the umbelliferae family. It is oleo gum resin obtained from the rhizome and root of plant. This spice is used as a digestive aid, in food as a condiment and in pickles. It is used in modern herbalism in the treatment of hysteria, some nervous conditions, bronchitis, asthma and whooping cough. It was at one time employed in the treatment of infantile pneumonia and fl atulent colic. The gum resin is antispasmodic, carminative, expectorant, laxative, and sedative. The volatile oil in the gum is eliminated through the lungs, making this an excellent treatment for asthma. The odor of asafoetida is imparted to the breath, secretions, fl atus, and gastric eructations. Its properties are antispasmodic, expectorant, stimulant, emmenagogue and vermifuge. Asafoetida has also been used as a sedative. It also thins the blood and lowers blood pressure. It is widely used in India in food and as a medicine in Indian systems of medicine like ayurveda. Asafoetida has been held in great esteem among indigenous medicines, particularly in Unani system from the earliest times.
Keywords: Ferula asafoetida; spice; umbelliferae